PELATIHAN PENGENALAN MASAKAN TRADISIONAL RIAU UNTUK MENINGKATKAN EKONOMI KELUARGA - Sofiyanita, Sofiyanita; Yasnel, Yasnel; Miterianifa, Miterianifa; Ernita, Mahdar; Rambe, Paijan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Traditional food is food that includes snacks and mixed ingredients that are used traditionally and have long developed specifically in Indonesian regions or communities. Traditional food is a form of aesthetic achievement about how a nation in a certain historical period is built with spirit and taste. This Community Service Activity aims to find out the efforts made to introduce traditional cakes to the community and training on how to make them. The method of this Community Service Activity is carried out by mentoring and training in processed food products. The results of this Community Service Activity show that by introducing and holding training in making traditional food, it can improve the family economy and be able to meet daily needs.